Organic Nanocrystal Fabrication Using the Process of Resonant Second-Harmonic Generation of Light - Miniewicz, Andrzej; Ślemp, Michalina; Pfleger, Jiri (ACS omega, 2021)
Laser ablation with the use of ultra-short laser pulses is a widely used technique for the fabrication of nanoparticles of metals, inorganic and hybrid materials. However, fabrication of fragile organic nanocrystals via laser ablation is rarely used due to easy photodegradation of molecules. The method employing laser irradiation of the target material is beneficial as no other chemicals are used in the production of nanoparticles, except for a given material and a solvent. In this work, we test the concept of formation of nonlinear optical (NLO) organic nanocrystals dispersion in water by irradiation of the microcrystals of the NLO material with nonabsorbed infrared nanosecond light pulses. These pulses, due to a nonlinear optical process active in a noncentrosymmetric organic crystal, such as those studied in this work, DCNP dye (3-(1,1-dicyanoethenyl)-1-phenyl-4,5-dihydro-1H-pyrazole), produce nanosecond pulses of second-harmonic (SH) light. Due to doubling of photon energy, they are reabsorbed in the volume of DCNP microcrystals and thermal shocks fracture them into nanometer size crystals. To the best of our knowledge, such process and its interpretation have not been described yet in the literature.